ASSESMENT OF QUALITY OF LIFE AND OXIDATIVE STRESS IN TUBERCULOSIS PATIENTS VISITING DIRECTLY OBSERVED TREATMENT SHORT COURSE CENTRES OF WARANGAL - V, Kavitha; B, SRINIVAS; P, Shashikanth; B, Muralikrishna (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: Tuberculosis (TB) is a disease associated with a wide range of respiratory symptoms. It remains a major public health problem worldwide. In TB, oxidative stress is a result of tissue inflammation, poor dietary intake of micronutrients due to illness, and free radical burst from activated macrophages. In recent years, efforts have been dedicated for assessing the health-related quality of life (HRQoL) in TB patients. The objectives of the study were to evaluate the impairment of HRQoL in TB patients using by DR-12 questionnaire and to estimate oxidative stress parameters such as malondialdehyde (MDA), glutathione (GSH), vitamins A, and C in TB patients. Methods: A total of 142 patients meeting the study criteria were recruited in the study to evaluate HRQOL. The patients were administered with DR-12 questionnaire at 0 week, 4 weeks and at the end of intensive phase of the treatment. A paired t-test was applied and a p<0.05 was considered as significant. 40 patients meeting the study criteria were recruited for assessment of oxidative stress parameters. The blood samples were assessed for the concentration of MDA, GSH, vitamin A, and vitamin C using suitable methods. Results: A significantly higher HRQOL scores were observed at the end of intensive phase of the treatment for both pulmonary and extrapulmonary TB patients. There was a significant improvement in their QOL (p<0.05). An increased oxidative stress was obtained in plasma of TB patients as compared to normal healthy controls. There was a significant increase in the MDA levels of TB patients (7 times greater than control) when compared to normal population. There was a double decrease in GSH and vitamin A concentrations in TB cases compared with controls. The plasma levels of vitamin C in TB cases obtained thrice lesser in TB cases than the control population. Conclusion: The study showed that in TB patients free radical activity is quite high and antioxidant levels are low. A suitable antioxidant therapy may improve QoL and prove beneficial supplementation for fast recovery. Keywords: Tuberculosis, Health-related quality of life, Directly observed treatment short course, DR-12 score, Antioxidants, Free radicals.